Pengembangan Modul Kimia SMA Berbasis STEM Pada Materi Termokimia - Teuku Badlisyah; Sabarni Sabarni; Anjas Rioga Novalta; Mellyzar Mellyzar (Peneliti.net, 2022)
The ineffectiveness of teaching materials is characterized by the complexity of the language for the chemistry textbooks and to maximize the goals of the 2013 curriculum which is the background for be developed of STEM (Science, Technology, Engineering, and Mathematics) based modules on thermochemistry subject at SMA Negeri 2 Banda Aceh. The purpose of this researching was to develop teaching material products in order to fixed the problems that found in SMA Negeri 2 Banda Aceh by looking at the validity of the products developed through expert validator assessments and seeing feedback from the responses of teachers and students. Type of this research is development research using the ADDIE model as a research design. The instruments used in this development research were interview sheets, validation sheets, teacher response questionnaire sheets, and student response questionnaire sheets. After processing the data on the validation sheet, the total percentage validation average score is 90.3%, so it is included in the very valid category. The results of the teacher's response were included in the very good category, namely 85.3%, as well as the results of the responses obtained from the responses of 28 students, namely 92.7%. The research conclusion interpreted from the results of data processing obtained is that the STEM (Science, Technology, Engineering, and Mathematics) based module on thermochemical material developed at SMA Negeri 2 Banda Aceh is very valid and very good to use.